ANALYSIS OF THE INFLUENCE OF BEHAVIORAL ACCOUNTING ON VILLAGE FINANCIAL SYSTEMS IN KERINCI REGENCY - Deki Andriadi; Afrizal; Ilham Wahyudi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
In the current era of globalization, village financial reporting is needed by users of financial reports, both central and local governments. The village financial system is part of village financial reporting. This study delves into the intricate relationship between behavioral accounting and village financial systems within Kerinci Regency. By examining how behavioral accounting practices impact these systems, this research sheds light on the dynamics that govern financial management in local communities. Drawing on a comprehensive analysis of data collected from various villages, this study reveals noteworthy insights into the effects of behavioral accounting practices on financial decision-making processes. Through an empirical investigation, it becomes evident that behavioral accounting practices can significantly influence the financial behavior of village administrations. The study uncovers that certain behavioral biases and cognitive patterns among administrators can impact financial reporting accuracy and budget allocation strategies. Furthermore, the research underscores the significance of effective training and awareness programs to mitigate potential negative effects of behavioral biases in financial decision-making. This study underscores the vital role of behavioral accounting in shaping the financial landscape of village systems. By recognizing and addressing the behavioral factors that influence financial decisions, village administrations can enhance the effectiveness and transparency of their financial management practices. These findings provide valuable insights for policymakers, administrators, and stakeholders seeking to improve the financial sustainability and accountability of village systems in Kerinci Regency and similar contexts.